Antibacterial non-woven nanofibers of curcumin acrylate oligomers - Killi, Naresh; Paul, Vejendla Luke; Gundloori, Rathna Venkata Naga (New Journal of Chemistry, 2015)
Two new (meth) acrylate monomers, namely, 4-((1E,6E)-7-(4'-hydroxy-3-methoxyphenyl)-3,5-dioxohepta-1,6-dienyl)-2-m ethoxyphenyl acrylate or curcumin monoacrylate (CmA) and 4-((1E, 6E)-7-(4'-hydroxy-3-methoxyphenyl)- 3,5-dioxohepta-1,6-dienyl)-2-methoxyphenyl methacrylate or curcumin monomethacrylate (CmMA), are synthesized by reacting (1E, 6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-dione (curcumin) with acryloyl chloride and methacryloyl chloride, respectively. The respective derivatives are polymerized by free radical polymerization using an initiator, 2,2-azobisisobutyrontrile (AIBN), to obtain the oligomer of curcumin monoacrylate (OCM) and the oligomer of curcumin monomethacrylate (OCMA). The oligomers are characterized by FTIR, H-1 NMR and UV-vis spectroscopy. The molecular weights of the oligomers are determined by GPC to range between 2000 and 5500 Da. The melting temperature (T-m) and degradation temperature of the respective oligomers are evaluated by thermal analysis. The melting temperature of the oligomers ranged from 195 to 197 degrees C. Antibacterial studies are evaluated against Staphylococcus aureus, in which the minimum inhibitory concentration (MIC) of OCA1 is 27 mg mL(-1). The blends of the individual oligomers with poly(lactic acid) are electrospun to obtain the respective non-woven nanofiber mats. Nanofibers are formed, with the diameter ranging from 400 to 750 nm, and the nanofiber mats are porous. Because the nanofiber mats are antibacterial and highly porous, they may have potential application as a wound dressing material for tissue regeneration.

Design and fabrication of mechanically strong nano-matrices of linseed oil based polyesteramide blends - Killi, Naresh; Dhakare, Runali Arjun; Singam, Amarnath; Lokanadham, Metta; Chitikeshi, Harshavardhan; Gundloori, Rathna Venkata Naga (Medchemcomm, 2016)
New nanomaterials of bio-origin with improved mechanical properties are in demand for biomedical application. Therefore, we propose to design and fabricate bioactive nano-matrices with good mechanical strength using polyesteramides derived from linseed oil. Polyesteramide was synthesized from linseed oil and blended with poly(L-lactide) and human serum albumin to enhance the mechanical strength, biodegradation, biocompatibility and hydrophilicity. The various blend solutions with and without drugs (triclosan and metronidazole) were electrospun into non-woven nano-matrices. The morphology of the nano-matrices represented smooth and fine nanofibers with the diameter ranging from 300 to 400 nm. Drug binding efficiency, cytotoxicity, hydrophilicity, thermal and mechanical studies indicated their suitability as biomaterials. To demonstrate their utility, the drug release kinetics and antibacterial properties were evaluated. The metronidazole loaded nano-matrices showed drug release up to 8 h, beyond which no release was observed until 72 h. Antibacterial studies were done using the drugs triclosan and metronidazole. The antibacterial activity of the drug loaded nanofiber mats increased with the increase in drug concentration. The uniqueness of the developed nano-matrices of polyesteramide blends is that their mechanical strength is 3-fold higher than that of the nano-matrices of poly(L-lactide), which is one of the essential features of these nano-matrices to be used as a biomaterial for biomedical applications.

Polyhydroxyalkanoates as biomaterials - Bhagyashri, S.; Gadgil, Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2017)
Polyhydroxyalkanoates (PHAs) are biopolymers synthesized by bacteria under unbalanced growth conditions. These biopolymers are considered as potential biomaterials for future applications because they are biocompatible, biodegradable, and easy to produce and functionalize with strong mechanical strength. Currently, PHAs are being extensively innovated for biomedical applications due to their prerequisite properties. The wide range of biomedical applications includes drug delivery systems, implants, tissue engineering, scaffolds, artificial organ constructs, etc. In this article we review the utility of PHAs in various forms (bulk/nano) for biomedical applications so as to bring about the future vision for PHAs as biomaterials for the advancement of research and technology.
Keywords: Biomedical Applications; Cancer-therapy; Drug-delivery Systems; In-vitro; Molecular-weight; Poly(Ester Urethane)S; poly(ethylene glycol); Regenerative Medicine; Tissue Engineering Applications; Vitro Antibiotic Release

Nanobased intravenous and transdermal drug delivery systems - Gundloori, Rathna V. N.; Singam, Amarnath; Killi, Naresh (Applications of Targeted Nano Drugs and Delivery Systems, 2019)
In this chapter we bring in the collective information about intravenous and transdermal nano drug delivery systems (DDSs), which include different kinds of constituents used for the design of nano DDSs, their various forms, methods, and characterization of nanoformulations.

Polyesteramide of neem oil and its blends as an active nanomaterial for tissue regeneration - Killi, Naresh; Pawar, Anil Tukaram; Gundloori, Rathna V. N. (ACS Applied Bio Materials, 2019)
Neem oil gained importance due to its antibacterial properties. Therefore, it is extensively being used for various applications. Oils can be polymerized as a polyesteramide to extend their utility as biomaterials. In our studies, we synthesized polyesteramide from neem oil and various compositions of blends were prepared with the drug, chlorohexidine digluconate (CH) to develop a nanomaterial for tissue regeneration. The studies such as cytotoxicity, biodegradable, antibacterial, in vitro drug release, in vivo wound healing, and histopathological studies were performed to identify their potential for tissue regeneration. In vivo wound healing studies of the nanofiber mats with and without CH recorded a faster healing rate as compared to the commercial cream (povidone–iodine). Most importantly, there was no requirement of repeated application of nanofiber mats during the treatment. The histopathology studies also suggested the re-epithelialization of the wounds. Hence, these nanomaterials are considered to be environmentally safe scaffolds for efficient tissue regeneration applications.

Polyhydroxyalkanoates as biomaterials (vol 8, pg 1774, 2017) - Gadgil, Bhagyashri S. Thorat; Killi, Naresh; Rathna, Gundloori V. N. (MedChemComm, 2019)
Correction for `Polyhydroxyalkanoates as biomaterials' by Bhagyashri S. Thorat Gadgil et al., Med. Chem. Commun., 2017, 8, 1774-1787.

Blends of neem oil based polyesteramide as nanofiber mats to control Culicidae - Konchada, Sravanya; Killi, Naresh; Sayyad, Shahebaz; Gathalkar, Ganesh B.; Gundloori, Rathna V. N. (RSC Advances, 2020)
Mosquitoes act as vectors for several disease-causing microorganisms and pose a threat to mankind by transmitting various diseases. There are different conventional methods to repel or kill these mosquitoes for avoiding susceptibility against infections. However, to overcome the difficulties with conventional methods, new advanced materials are being studied. For the first time, we report developing a nanofiber mat with a controlled release of insecticide to repel or detain the mosquitoes. Briefly, various blend compositions were prepared by manipulating the ratio of neem oil-based polyesteramide (PEA) and polycaprolactone (PCL) immobilized with insecticide, transfluthrin (Tf). The blend solutions were electrospun to get non-woven nanofiber mats, and these nanomaterials were characterized by various spectroscopic techniques to understand their physicochemical properties. The surface morphology was analyzed using environmental scanning electron microscopy (E-SEM), and the diameter of the nanofibers was in the range of 200 to 450 nm. Further, thermal and mechanical properties were evaluated to understand the stability of nanofiber mats. In vitro drug release studies of nanofiber mat PPT-1335 showed controlled and sustained release of Tf, with similar to 35% of Tf released in 24 h. However, a film of the same composition (PPT-1335) showed similar to 5% of Tf release within 24 h. Moreover, in vivo bio-efficacy studies suggested the mortality of mosquitoes was about 50% with PP-133, which was further increased to 100% within 12 h in the presence of Tf (PPT-1335). However, 60% mortality of mosquitoes was observed with the film of PPT-1335. Hence, the nanofiber mat showed better efficacy against mosquitoes as compared to the film of the same composition. The degradation studies under various conditions revealed biocompatibility of the developed nanofiber mats with the ecosystem.

Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions - Patel, Pratikshkumar R.; Pandey, Komal; Killi, Naresh; Gundloori, Rathna Venkata Naga (Polymer Engineering and Science, 2021)
A hybrid of poly-l-lactic acid (PLA) and poly-epsilon-caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45 degrees with the increase in EA concentration. The rate and extent of swelling was increased 3-folds with the addition of EA. Release studies of NM showed maximum amount of MTz was released with the increase in MTz concentration (>85%). The MTz interaction with EA and structure stability of EA was confirmed from fluorescence and circular dichroism studies. NM showed increase in inhibition of bacterial growth of Staphylococcus aureus and Escherichia coli with the increase in MTz concentration. Cell viability of the NM was >80% and also, the cell proliferation increased as EA content increased. NM hemolytic activity was less than 5% suggesting compatibility. Hence, results concluded that EA had regulated hydrophobicity, promoted cell interactions, and proliferation and therefore, NM is considered safe for tissue regeneration.
Keywords: Biocompatibility; Biomaterials; drug delivery systems; egg albumin; electrospinning; nanofibers; polyesters

One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization

PEGylated ethyl cellulose micelles as a nanocarrier for drug delivery - Singam, Amarnath; Killi, Naresh; Patel, Pratikshkumar R.; Gundloori, Rathna V. N. (RSC Advances, 2021)
Natural polymers provide a better alternative to synthetic polymers in the domain of drug delivery systems (DDSs) because of their renewability, biocompatibility, and low immunogenicity; therefore, they are being studied for the development of bulk/nanoformulations. Likewise, current methods for engineering natural polymers into micelles are in their infancy, and in-depth studies are required using natural polymers as controlled DDSs. Accordingly, in our present study, a new micellar DDS was synthesized using ethyl cellulose (EC) grafted with polyethylene glycol (PEG); it was characterized, its properties, cell toxicity, and hemocompatibility were evaluated, and its drug release kinetics were demonstrated using doxorubicin (DOX) as a model drug. Briefly, EC was grafted with PEG to form the amphiphilic copolymers EC-PEG1 and EC-PEG2 with varying PEG concentrations, and nano-micelles were prepared with and without the drug (DOX) via a dialysis method; the critical micelle concentrations (CMCs) were recorded to be 0.03 mg mL(-1) and 0.00193 mg mL(-1) for EC-PEG1 and EC-PEG2, respectively. The physicochemical properties of the respective nano-micelles were evaluated via various characterization techniques. The morphologies of the nano-micelles were analyzed via transmission electron microscopy (TEM), and the average size of the nano-micelles was recorded to be similar to 80 nm. In vitro, drug release studies were done for 48 h, where 100% DOX release was recorded at pH 5.5 and 52% DOX release was recorded at pH 7.4 from the micelles. In addition, cytotoxicity studies suggested that DOX-loaded micelles were potent in killing MDA-MB-231 and MCF-7 cancer cells, and the blank micelles were non-toxic toward cancerous and normal cells. A cellular uptake study via fluorescence microscopy indicated the internalization of DOX-loaded micelles by cancer cells, delivering the DOX into the cellular compartments. Based on these studies, we concluded that the developed material should be studied further via in vivo studies to understand its potential as a controlled DDS to treat cancer.

Combinatorial therapy using RNAi and curcumin nano-architectures regresses tumors in breast and colon cancer models - Kumar, Aviral; Singam, Amarnath; Swaminathan, Guruprasadh; Killi, Naresh; Tangudu, Naveen Kumar; Jose, Jedy; Gundloori, Rathna V. N.; Kumar, Lekha Dinesh (Nanoscale, 2022)
Cancer is a debilitating disease and one of the leading causes of death in the world. In spite of the current clinical management being dependent on applying robust pathological variables and well-defined therapeutic strategies, there is an imminent need for novel and targeted therapies with least side effects. RNA interference (RNAi) has gained attention due to its precise potential for targeting multiple genes involved in cancer progression. Nanoparticles with their enhanced permeability and retention (EPR) effect have been found to overcome the limitations of RNAi-based therapies. With their high transportation capacity, nanocarriers can target RNAi molecules to tumor tissues and protect them from enzymatic degradation. Accumulating evidence has shown that tyrosine kinase Ephb4 is overexpressed in various cancers. Therefore, we report here the development and pre-clinical validation of curcumin-chitosan-loaded: eudragit-coated nanocomposites conjugated with Ephb4 shRNA as a feasible bio-drug to suppress breast and colon cancers. The proposed bio-drug is non-toxic and bio-compatible with a higher uptake efficiency and through our experimental results we have demonstrated the effective site-specific delivery of this biodrug and the successfull silencing of their respective target genes in vivo in autochthonous knockout models of breast and colon cancer. While mammary tumors showed a considerable decrease in size, oral administration of the biodrug conjugate to Apc knockout colon models prolonged the animal survival period by six months. Hence, this study has provided empirical proof that the combinatorial approach involving RNA interference and nanotechnology is a promising alliance for next-generation cancer therapeutics.